Cyber Surveillance dalam Penanganan Tindak Pidana Terorisme: Antara Keamanan Nasional dan Hak Privasi - Khayrunaas Mulyana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The development of digital technology has transformed terrorism into a cyber-based crime, prompting states to implement cyber surveillance as a tool to safeguard national security. However, such practices raise concerns regarding violations of privacy rights as fundamental human rights. This article examines the concept and practice of cyber surveillance in handling terrorism in Indonesia, the legal position of privacy rights under national law and human rights instruments, and proposes an ideal regulatory model to balance national security and privacy protection. The study concludes that the right to privacy can be limited by law, but there needs to be comprehensive, proportional and accountable regulations in the implementation of cyber surveillance.